Modelling Turbine Vibration in Terms if its Load Variation - T. J. Chalko; D. X. Li (International Journal of Rotating Machinery)
This paper is based on a case history of a 650 MW turbine-generator, which changed its vibration significantly every time when a change of its thermal/electrical load was made. Significant changes of vibration amplitude and phase distribution along the shaft indicated the contribution of different modes of vibration. Interestingly, vibration of other identical units manufactured by the same manufacturer were not sensitive to load variation. A vibration monitoring system, relying on observing slow trends in vibration data, was not able to interpret the significant vibration changes. In particular, it was not clear, whether or not there was a fault in the system and whether or not the unit was safe to operate. The paper presents problem modelling, analysis and the explanation for vibration changes. Presented analysis explains that vibration changes were not associated with the fault in the system but they were a natural response of the system to parameter change.